WOMEN'S LEADERSHIP MANAGEMENT IN GENDER PERSPECTIVE IN LAMPUNG PROVINCE UNIVERSITIES - Hadiati, Eti; Kamil, Badrul; Dwiyanto, Agus; Setianingrum, Diah Ayu; Setiyo, Setiyo (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2024)
Gender inequality and injustice in an organization or company, educational institutions included, can still be found. The cause of these differences often occurs due to the influence of gender bias which is still commonly found in reference books, where women are positioned as "second class" society assuming that women's abilities only in domestic affairs and only men who can only play roles as leaders in public affairs. The purpose of this study was to examine and provide an overview of women's leadership in a gender perspective at universities in Lampung Province. This study utilizes qualitative research methods with in-depth interview and documentation as data collection techniques. This study involves the Rector, Vice Rector, Dean and Dean Deputy of various universities in Lampung Province as the subject of the research. The data collection was performed on each different set of times since the depth comprehension through interview is required in this study. The results indicated that female leaders in universities in Lampung Province have a tendency to adopt a feminine-transformational leadership style. It can be seen that up to now, female leaders in universities in Lampung Province have succeeded in improving the performance, morality and performance of the ranks, staff and subordinates which have resulted in brilliant achievements and well-run work programs that have been planned. For further research, it is to be expected that future study could involve more variables and expand the scope of research for the betterness.